2017
DOI: 10.1109/tnsre.2016.2619742
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Programmable Tactile Displays on Spatial Learning Skills in Children and Adolescents of Different Visual Disability

Abstract: Vision loss has severe impacts on physical, social and emotional well-being. The education of blind children poses issues as many scholar disciplines (e.g., geometry, mathematics) are normally taught by heavily relying on vision. Touch-based assistive technologies are potential tools to provide graphical contents to blind users, improving learning possibilities and social inclusion. Raised-lines drawings are still the golden standard, but stimuli cannot be reconfigured or adapted and the blind person constantl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 43 publications
0
32
0
Order By: Relevance
“…The results of these studies are thus missing in this systematic review, and further research should indicate whether interventions investigated in these studies might be effective for improving quality of life, participation, and functioning in children with visual impairment. Moreover, some articles were more experimental in nature, comparing, for example, 2 methods for visual search, and reporting on the results over time 25,64 ; however, these studies did not include information on pretest data and were therefore also omitted in this systematic review. In addition, studies not published in English, Dutch, French, or German were excluded in this systematic review, because of the difficulties with interpretation of the results.…”
Section: Strengths and Limitations Of This Systematic Reviewmentioning
confidence: 99%
“…The results of these studies are thus missing in this systematic review, and further research should indicate whether interventions investigated in these studies might be effective for improving quality of life, participation, and functioning in children with visual impairment. Moreover, some articles were more experimental in nature, comparing, for example, 2 methods for visual search, and reporting on the results over time 25,64 ; however, these studies did not include information on pretest data and were therefore also omitted in this systematic review. In addition, studies not published in English, Dutch, French, or German were excluded in this systematic review, because of the difficulties with interpretation of the results.…”
Section: Strengths and Limitations Of This Systematic Reviewmentioning
confidence: 99%
“…When studying spatial performance, such as in geometry tasks, it is important to know the onset of visual disability because students who have had visual experience for only one year or less in childhood have considerable advantage in looking at and perceiving shapes (Millar, 2008). The age of onset of the visual condition is only adequately described in two articles (Leo et al, 2017;Oliveira et al, 2012), and only four studies reported eye diagnoses (Bateman et al, 2018;Bouck et al, 2011;Bouck et al, 2016;Leo et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…and therefore, such information is important when considering the results of a study. Leo et al (2017) have carefully outlined visual function, eye diagnosis, and age, and have considered these variables in their measurements. The effect results of programmable tactile displays on spatial learning skills are thus both credible and interesting.…”
Section: Discussionmentioning
confidence: 99%
“…Also, we could have not displayed 16 symbols with higher resolutions on a 30x32 display, therefore the experimental manipulation could have made the comparison among resolutions tricky. In another study [29], we have considered 6x6 symbols shaped as crosses and shown that they can be the basis for increasing spatial learning skills in blind children and adolescents.…”
Section: Discussionmentioning
confidence: 99%